Molecular resolution imaging by repetitive optical selective exposure - Gu, Lusheng; Li, Yuanyuan; Zhang, Shuwen; Xue, Yanhong; Li, Weixing; Li, Dong; Xu, Tao; Ji, Wei (Nature methods, 2019)
We introduce an interferometric single-molecule localization method for super-resolution fluorescence microscopy. Fluorescence molecules are located by the intensities of multiple excitation patterns of an interference fringe, providing around a twofold improvement in the localization precision compared with the conventional imaging with the same photon budget. We demonstrate this technique by resolving nanostructures down to 5 nm in size over a large 25 × 25 μm 2 field of view. Repetitive optical selective exposure (ROSE) is an interferometric single-molecule localization microscopy method offering twofold improvement in lateral resolution with the same photon budget compared with conventional approaches.